2003
DOI: 10.1053/jhep.2003.50209
|View full text |Cite
|
Sign up to set email alerts
|

A Role of Autoantibody–Mediated Platelet Destruction in Thrombocytopenia in Patients With Cirrhosis

Abstract: Thrombocytopenia is a common manifestation in patients with liver cirrhosis (LC), but its underlying mechanism remains controversial. This study examined the role of anti-platelet autoimmunity in cirrhotic thrombocytopenia by determining the autoantibody response to GPIIb-IIIa, a major platelet surface autoantigen recognized by anti-platelet antibodies in patients with idiopathic thrombocytopenic purpura (ITP). Circulating B cells producing anti-GPIIb-IIIa antibodies as well as platelet-associated and plasma a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
65
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(68 citation statements)
references
References 43 publications
2
65
0
1
Order By: Relevance
“…The incidence of endemic HCV-ITP in 294 chronic patients was 10%, which increased to 32% with advanced liver disease. 15 The frequency of B-cell production of anti-GPIIb-IIIa Ab was 27-fold greater than with control cells in 37 HCV-ITP patients with cirrhosis 17 ; and an inverse correlation was found between platelet count and B-cell anti-GPIIb-IIIa Ab production in 51 patients with liver cirrhosis (73% with hepatitis C). This would suggest some degree of specificity.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The incidence of endemic HCV-ITP in 294 chronic patients was 10%, which increased to 32% with advanced liver disease. 15 The frequency of B-cell production of anti-GPIIb-IIIa Ab was 27-fold greater than with control cells in 37 HCV-ITP patients with cirrhosis 17 ; and an inverse correlation was found between platelet count and B-cell anti-GPIIb-IIIa Ab production in 51 patients with liver cirrhosis (73% with hepatitis C). This would suggest some degree of specificity.…”
Section: Introductionmentioning
confidence: 97%
“…14 Patients with HCV commonly develop immunologic thrombocytopenia (HCV-ITP) that correlates with severity of disease (eg, chronic active hepatitis, cirrhosis). [15][16][17] The incidence of HCV-ITP in a series of 368 HCV Japanese patients with chronic persistent or chronic active hepatitis was 41%. The incidence of endemic HCV-ITP in 294 chronic patients was 10%, which increased to 32% with advanced liver disease.…”
Section: Introductionmentioning
confidence: 99%
“…Another mechanism of thrombocytopenia in liver cirrhosis is anti-platelet autoantibody-mediated platelet destruction. Kajihara et al [10] have revealed a similar profile of the anti-glycoprotein Ⅱb/Ⅲa autoantibody response between patients with liver cirrhosis and those with ITP, and concluded that immune-mediated platelet destruction may contribute, at least in part, to cirrhotic thrombocytopenia. In the present case, an autoimmune response to platelets might have been induced or enhanced by the underlying liver cirrhosis.…”
Section: Discussionmentioning
confidence: 94%
“…17,18 Liver transplantation is known to resolve thrombocytopenia due to an increase in serum TPO and increased platelet production. 19,20 As splenomegaly is an important feature of portal hypertension, it is not surprising that splenic platelet sequestration is thought to be an important mechanism in the etiology of thrombocytopenia. Kinetic radiolabelled platelet studies do suggest splenic pooling, but they also report shorter platelet survival time, indicative of splenic destruction rather than mere splenic pooling.…”
Section: Discussionmentioning
confidence: 99%